Limit Cycles in Piecewise Smooth Van der Pol Equations (Journal of Nonlinear Modeling and Analysis, 2024)
This paper focuses on analyzing the properties of equilibrium pointsand limit cycles in two types of planar piecewise smooth slow-fast systems. Theright-half system is a classical van der Pol equation, while the left-half systemis either linear or quadratic. Additionally, we provide a detailed descriptionof the characteristics of limit cycles in these systems.
Keywords: Limit cycles; slow-fast systems; van der Pol equations.